O insulă a criticii şi a istoriei literare în epoca totalitarismului - Stancu Ilin (Revista de Istorie și Teorie Literară)
After the professor G. Calinescu was rejected from the University, in 1948, in unknown circumstances, being transferred as director of the Institute of Literary History and Folklore, all the commando team, guided by the dentist Ion Vitner, who took his place in the University, followed him, there, by ideological reasons. In 1957, when I was admitted at the Institute, Vitner’s place was taken by Mihai Novicov, as deputy director. At the Institute I have meet another Calinescu. He was like an father for his colleagues, treating them like his family. He was gentle, but straight to, when his “children” were making mistakes. The play, in the intellectual meaning of the word, has fulfilled his last years. He was dancing menuet, or acting in his plays, or reading the poetry of Baudelaire together with his younger disciples. One year after I was admitted at the Institute, I was designed by G. Calinescu as the scientific secretary. In this quality, I was having the duty to write the minutes of the meetings. Now, for the first time, we are publishing these minutes in their integrality, in series, in “The Revue of Literary History and Literary Theory”.